The Cut-off Values of Triglycerides - Glucose Index for Metabolic Syndrome Associated with Type 2 Diabetes Mellitus (Baghdad Science Journal, 2022)
The co-occurrence of metabolic syndrome with type 2 diabetes mellitus (T2DM) will potentiate the morbidity and mortality that may be associated with each case. Fasting triglycerides-glucose index (TyG index) has been recommended as a useful marker to predict metabolic syndrome. Our study aimed to introduce gender-specific cut-off values of triglycerides- glucose index   for diagnosing metabolic syndrome associated with type 2 diabetes mellitus. The data were collected from Baghdad hospitals between May - December 2019. The number of eligible participants was 424. National cholesterol education program, Adult Treatment Panel III criteria were used to define metabolic syndrome. Measurement of fasting blood glucose, lipid profile, HbA1c level, blood pressure, and anthropometric were done and the triglyceride-glucose index was calculated. Ethical approval and informed consent were obtained .SPSS was used to analyze the data. Diabetic patients with metabolic syndrome showed an increased level of TyG Index. The prevalence of metabolic syndrome increased with increased TyG index quartiles. The TyG-Index showed significant correlations with all components of metabolic syndrome. The optimal cut-off value revealed 9.14, 9.28 for males and females respectively. In conclusion, TyG index is a good predictor of the presence of MetS in T2DM the TyG index, just measured in one laboratory test, is simple, informative and more suitable for the detection of metabolic syndrome in Iraqi type 2 diabetes mellitus.